Bitter taste receptors of the common vampire bat are functional and show conserved responses to metal ions in vitro. Issue 1947 (31st March 2021) - Ziegler, Florian; Behrens, Maik
Abstract : The bitter taste sensation is important to warn mammals of the ingestion of potentially toxic food compounds. For mammals, whose nutrition relies on highly specific food sources, such as blood in the case of vampire bats, it is unknown if bitter sensing is involved in prey selection. By contrast to other bat species, vampire bats exhibit numerous bitter taste receptor pseudogenes, which could point to a decreased importance of bitter taste. However, electrophysiological and behavioural studies suggest the existence of functional bitter taste transmission. To determine the agonist spectra of the three bitter taste receptors that are conserved in all three vampire bat species, we investigated the in vitro activation of Desmodus rotundus T2R1, T2R4 and T2R7. Using a set of 57 natural and synthetic bitter compounds, we were able to identify agonists for all three receptors. Hence, we confirmed a persisting functionality and, consequently, a putative biological role of bitter taste receptors in vampire bats. Furthermore, the activation of the human TAS2R7 by metal ions is shown to be conserved in D. rotundus .